68Ga-fibroblast activation protein inhibitor PET/CT on gross tumour volume delineation for radiotherapy planning of oesophageal cancer. (May 2021) - Zhao, Liang; Chen, Shanyu; Chen, Sijia; Pang, Yizhen; Dai, Yaqing; Hu, Shenping; Lin, Li'e; Fu, Lirong; Sun, Long; Wu, Hua; Chen, Haojun; Lin, Qin
Highlights: 68 Ga-FAPI PET/CT showed favourable tumour-to-background contrast compared to 18 F-FDG PET/CT in oesophageal cancer. SUV thresholds of FAPI ×20%, 30%, 40%, and FDG ×40% showed similar lesion lengths compared with endoscopic examination. 68 Ga-FAPI PET/CT may provide additional information for target volume delineation to avoid tumour geographic misses. Abstract: Background and purpose: To compare 68 Ga-fibroblast activation protein inhibitor (FAPI) and 18 F-FDG PET/CT in imaging locally advanced oesophageal cancer, and evaluate the potential usefulness of 68 Ga-FAPI PET/CT on gross target volume (GTV) delineation aimed at radiotherapy planning for oesophageal cancer as compared with contrast-enhanced CT (CE-CT) and 18 F-FDG PET/CT. Materials and methods: Twenty-one patients with newly diagnosed oesophageal cancer who underwent both 18 F-FDG and 68 Ga-FAPI PET/CT scans were selected. GTVs of the primary tumours based on CE-CT (GTVCT ), PET/CT, and CE-CT plus PET/CT were delineated. Gross tumour lengths were measured by GTVs and endoscopy and recorded. Results: The 68 Ga-FAPI PET showed significantly higher radiotracer uptake than 18 F-FDG PET (median SUVmax 16.71 vs. 11.23; P  = 0.002) in the primary tumours. SUV thresholds of FAPI ×20%, 30%, 40%, and FDG ×40% showed similar lesion lengths compared with that in endoscopic examination ( P  > 0.05). GTVCT demonstrated the largest volume (median: 48.80 mm 3, range: 14.83–162.23 mm 3 ) than PET-based GTVs. For PET/CT-guided complementary contouring of GTVCT, four patients (19%) were increased by FAPI ×20% and 30%, two patients (9.5%) were increased by FAPI ×40%, and only one patient was increased by FDG ×40%. Furthermore, the volume of GTV based on CE-CT plus FAPI ×20%, 30%, and 40% showed no significant difference with GTVCT and planning target volume based CE-CT plus FAPI-PET and meets the organ at risk standard. Conclusion: The 68 Ga-FAPI PET/CT methodology showed favourable tumour-to-background contrast in oesophageal cancer and might provide additional information for target volume delineation and help avoid tumour geographic misses.